2020
DOI: 10.20473/jn.v15i2.20610
|View full text |Cite
|
Sign up to set email alerts
|

The Differences of Inpatients’ Satisfaction Level based on Socio-Demographic Characteristics

Abstract: Introduction: Assessing the quality of nursing care has become a global health issue. especially for caregivers and recipients of care in the inpatient department. Patient satisfaction is one of the  indicators to measure quality of nursing care. This study aimed to identify the differences of patient satisfaction level in inpatient ward based on socio-demographic characteristics at Siloam Hospitals Bali.Methods: This study was cross-sectional design with descriptive comparative and correlation methods. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Nursing services are an important part of quality and safety in hospital care and are a determining factor in patient satisfaction with treatment outcomes, satisfaction is a happy state and means satisfaction with an action or an event after the patient uses the service (Aboosalehi et al, 2022). Thus, nursing care is an important part in determining patient satisfaction (Dewi, Yanti and Saputra, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nursing services are an important part of quality and safety in hospital care and are a determining factor in patient satisfaction with treatment outcomes, satisfaction is a happy state and means satisfaction with an action or an event after the patient uses the service (Aboosalehi et al, 2022). Thus, nursing care is an important part in determining patient satisfaction (Dewi, Yanti and Saputra, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Health services can improve the quality of their services, if they know the level of patient satisfaction, in relation to the quality of service provided. On their research Dewi, et al [1] showed that the socio-demographic characteristics of patients affected patient satisfaction. In general, patients' expectations, their perceptions and past experiences related to health care, are the main determinants of patient satisfaction worldwide.…”
Section: Introductionmentioning
confidence: 99%